Gambaran Pelaksanaan Standar Pelayanan Farmasi Di Apotek DKI Jakarta Tahun 2003 - Purwanti, Angki; Harianto, Harianto; Supardi, Sudibjo (Majalah Ilmu Kefarmasian, 2004)
The service orientation of clinical pharmacy and community have been changed from focusing only managing the medicine as commodity to comprehensive service based on pharmaceutical care. Refer to that basic, ISFI with the cooperation of Min- istry of Health establish Standard of Pharmaceutical Service in Pharmacy. The stan- dard is aimed to ensure the service quality and shall be implemented in all Pharma- cies. The purpose of the study is to have an implementation overview Standard of Pharmaceutical Service in Pharmacy and the results may used for establishing the phase of implementation Standard of Pharmaceutical Service in Pharmacy. This study is a descriptive study, the data were compiled by using a question- naire, as respondents. Compiled data consist of pharmacy’s basic data, pharmacist’s basic data, implementation of non prescription drug’s service (section I), KIE’s ser- vice (section II), prescription drug’s service (section III) and management of medi- cine (section IV). The average score of implementation of section I is 60.18 (not good), section II is 31.84 (worse), section III is 64.22 (not good) , section IV 87.84 (good) and the overall average from section I to IV is 61.02 (not good)